2017
DOI: 10.1080/14786435.2017.1352106
|View full text |Cite
|
Sign up to set email alerts
|

Large spontaneous Hall effects in chiral topological magnets

Abstract: As novel topological phases in correlated electron systems, we have found two examples of non-ferromagnetic states that exhibit a large anomalous Hall effect. One is the chiral spin liquid compound Pr2Ir2O7, which exhibits a spontaneous Hall effect in a spin liquid state due to spin ice correlation. The other is the chiral antiferromagnets Mn3Sn and Mn3Ge that exhibit a large anomalous Hall effect at room temperature. The latter shows a sign change of the anomalous Hall effect by a small change in the magnetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Here we focus particularly on Mn 3 Sn which involve both Weyl physics [22,23] and antiferromagnetism with large Néel temperature of T N ∼420 K [24]. In Mn 3 Sn magneto-geometrical frustration in the Kagome lattice leads to non-collinear antiferromagnetic order causing Mn moments to lie in the ab-plane (Kagome-plane) with moments aligned at 120 0 with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus particularly on Mn 3 Sn which involve both Weyl physics [22,23] and antiferromagnetism with large Néel temperature of T N ∼420 K [24]. In Mn 3 Sn magneto-geometrical frustration in the Kagome lattice leads to non-collinear antiferromagnetic order causing Mn moments to lie in the ab-plane (Kagome-plane) with moments aligned at 120 0 with each other.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent theoretical and experimental progress has revealed that systems such as certain spin liquids and non-collinear antiferromagnets may exhibit a large Hall response in zero applied magnetic field (anomalous Hall effect or AHE) despite a vanishing magnetization 15,[24][25][26][27][28][29][30][31] . Because the AHE has the same symmetry requirements as the MOKE 32 , it is possible that the same class of antiferromagnets may exhibit a Kerr rotation.…”
mentioning
confidence: 99%
“…Non-collinear antiferromagnets such as Mn 3 Sn and Mn 3 Ge have recently emerged as a fascinating class of materials that can exhibit a large anomalous Hall effect (AHE) despite having a negligibly small net magnetic moment [1][2][3][4][5][6]. The AHE can arise in these and related antiferromagnetic (AF) materials when the underlying spin order not only breaks time-reversal symmetry but also lacks additional spatial symmetries that would otherwise force the AHE to vanish.…”
mentioning
confidence: 99%